-3
Explanation:
If f(x)=f(-1) then you just fill in -1 where x is.
2*-1-1
-2-1
-3
Answer:
f(2)=5, f(-2)=-7
Step-by-step explanation:
Step 1 : f(2)=3(x)-1
f(2)=5
Step 2 : f(-2)=3(x)-1
f(-2)=-7
Answer:
3rd one or infinite
Step-by-step explanation:
Answer:
B: y = -2/3x - 10/3
Step-by-step explanation:
The point is at (-2,-2), therefore when you input -2 into the desired equation, it should yield -2 as our output. If we use the equation B, the equation becomes
-4/3 - 10/3 which is -6/3. After dividing it we get -2 as the output.
To find the line yourself we use the point slope formula
y - y1 = m(x - x1)
The line is parallel to the one on the graph so the slope or <em>m</em> is equal to -2/3
We input the coordinates we want for y1 and x1.
y - (-2) = -2/3 (x - (-2))
y + 2 = -2/3x - 4/3
y + 6/3 = -2/3x - 4/3
y = -2/3x - 10/3
Answer:9/4
Step-by-step explanation:
99/8*2/11=9/4*1/1=9/4
You can cancel out 99 and 11 to 9 and 1 as they are multiples of eac hother and you can do the same for 8 and 2 to 4 and 1